Australian private healthcare staff perspectives on patient reported experience measures (PREMs): a qualitative interview study - Krista Verlis; Kirsten McCaffery; Tessa Copp; Rachael Dodd; Brooke Nickel; Rebekah Laidsaar-Powell (Journal of Patient-Reported Outcomes)
Abstract Objective Patient reported experience measures (PREMs) are common tools utilised in hospitals to support quality improvements, allow consumers to provide feedback on care experiences and can be used to support consumers’ hospital selections. This study aimed to understand the views and opinions of private hospital staff on PREM use and the utility of PREMs as a consumer decision-making tool. Method Qualitative, semi-structured interview study conducted via telephone between March-June 2023. Participants (n = 10) were recruited from major private healthcare providers in Australia with half representing hospital-based staff and the other half corporate head office staff who work in patient experience and quality. Interviews were audio-recorded, transcribed, and analysed thematically. Results PREM benefits included an understanding of patient experience that improved provision of patient centred care with feedback acting as catalyst for change, to corporate-level strategic initiatives that address specific issues. Drawbacks of PREM reporting included concerns around skewed results by biased respondents, and completion based on hard to alter items (e.g., infrastructure) or on matters outside of hospital control (e.g., insurance). Staff had mixed reactions to consumers using PREMs results when selecting a hospital, some advocated for transparency while others feared consumers would misinterpret the data. Conclusions Improved real-time reporting of PREMs, learning from other industries about recording customer experience, and mandatory reporting by private hospitals could further the benefits of PREM measurement in private healthcare. Recognised was the need for PREMs to be displayed in a readily understood way so those with limited health literacy can correctly interpret.